Analisis dan Perancangan Ulang User Interface dan User Experience Sistem Informasi Kuliah Online Universitas Muhammadiyah Riau Menggunakan Metode Design Thinking - Mualfah, Desti; Kamal Saputra, Taufiq; Firdaus, Rahmad (JURNAL FASILKOM, 2024)
Sistem Informasi Kuliah Online (Sikuli) is an online learning platform developed by the Universitas Muhammadiyah Riau (UMRI) to support teaching and learning activities during the Covid-19 pandemic. The application has functionality in implementing online learning because it has benefits for lecturers and students. However, Sikuli has shortcomings in appearance and functionality that need to be further developed. To facilitate the development of the Online Lecture Information System, a User Interface and User Experience implementation technique is needed using the Design Thinking approach to redesign the Sikuli interface and user experience. User needs were identified through a questionnaire using the System Usability Scale (SUS) method for 114 UMRI students. As a result, 36.8% of respondents considered the layout of Sikuli's features and content very inadequate, while 20.2% considered it inadequate. After the redesign, the application was retested with SUS and obtained a score of 79.58, which is included in the "Excellent" category. This shows that the redesign has succeeded in increasing user satisfaction and experience.